Determination of Meprin Alpha Enzyme and its Relationship with Some Antioxidants and Interleukin 12 in the Blood Serum of Patients with Colon Cancer - Hussein Mahmoud Khalaf; Wasan Nazhan Hussein; Alaa Hassan Mussttaf (Diyala Journal of Medicine)
Background: Colon cancer is an uncontrolled growth of cells that begins in a part of the large intestine called the colon. The colon is the first and longest section of the large intestine. The possible causes of colon cancer are genetic, environmental and nutritional factors. This study was prepared to help in identifying the causes and predicting the occurrence of colon cancer.